POSSIBLE DIRECTIONS FOR CHANGE IN MUSIC COURSE (WITH SPECIAL REFERENCE TO DEVI AHILYA UNIVERSITY): संगीत के पाठ्यक्रम में परिवर्तन की संभावित दिशाएं (देवी अहिल्या विश्वविद्यालय के विशेष संदर्भ में) - Vad, Suvarna (International Journal of Research -GRANTHAALAYAH, 2015)
It is necessary to analyze each and every point of the subject while proposing the topic presented, such as why change in the curriculum of music? And why special reference to Devi Ahilya University? Having completed my entire education at Devi Ahilya University, I have been in touch with the vocabulary course for the last 36 years. The curriculum of D.A.V.V.’s music course remained the same for many years, but with the introduction of subjects like computer and commerce in girls colleges, there was a change in the thinking of the students. Earlier, the number of female students in the Faculty of Arts was very appreciable, but gradually the students started taking commerce and computer subjects. The reason for this was the employment of these subjects. Due to comparatively higher employment prospects in these subjects, it was natural for the students to take admission in these subjects. Gradually, the number of female students in the Faculty of Arts has reduced and in it also the fine arts like music, painting, etc. have become more and less. प्रस्तुत विषय की प्रस्तावना करते समय विषय के प्रत्येक बिन्दु का विश्लेषण करना आवश्यक है जैसे संगीत के पाठ्यक्रम में परिवर्तन क्यों? तथा देवी अहिल्या विश्व विद्यालय का विशेष संदर्भ क्यों? मेरी सम्पूर्ण शिक्षा देवी अहिल्या विश्वविद्यालय में होने , मैं गत 36 वर्षों से कंठ संगीत के पाठ्यक्रम के सम्पर्क में हूँ। दे.अ.वि.वि का कंठ संगीत का पाठ्यक्रम कई वर्षों तक एक समान ही रहा परन्तु कम्प्यूटर एवं कॉमर्स जैसे विषयों के कन्या महाविद्यालयों में पदार्पण होने से छात्राओं की सोच में परिवर्तन आया। पूर्व में कला संकाय में छात्राओं की संख्या काफी सराहनीय होती थी परन्तु धीरे धीरे छात्राओं ने कॉमर्स एवं कम्प्यूटर विषय लेने शुरू किए। इसका कारण इन विषयों का रोजगारोन्मुख होना था। रोजगार की सम्भावनाएँ इन विषयों में तुलनात्मक रूप से अधिक होने से छात्राओं का इन विषयों में प्रवेश लेना स्वाभाविक था। कला संकाय में धीरे धीरे छात्राओं की संख्या कम हो गई है और उसमें भी ललित कला जैसे संगीत,चित्रकला आदि में और भी कम होती गई।